ASSA13-08-5 Safety and Long-Term Efficacy of Left Subclavian Artery Coverage During Thoracic Endovascular Aortic Repair. (29th April 2013) - Xiaozeng, Wang; Quanmin, Jing; Yaling, Han; Haiwei, Liu; Fanfei, Wang
Abstract : Objective: To observe the safety and long-term efficacy of left subclavian artery (LSA) coverage during thoracic endovascular aortic repair (TEVAR). Methods: Retrospectively analysed the clinical data and outcomes perioperatively and during follow-up in 278 patients who were suffered from Stanford B aortic dissection and accepted TEVAR between April 2002 and July 2011. Among those patients, 77 had lesions that required LSA coverage and 201 had their LSA uncovered. Results: The patients with coronary artery disease and hypertension were more often seen in LSA-uncovered group, while those with penetrating atherosclerotic ulcer were less seen in this group (P < /span > <0.05). The other clinical baseline data had no statistics differences between two groups. The success ratios of TEVER were both 100% in two groups. The proximal landing zones were shorter (8.0 ± 6.5mm vs 28.3 ± 10.1mm, P = 0.000) while the aortas covered by stent grafts were longer (132.6 ± 24.7mm vs 122.0 ± 38.9mm, P = 0.011) in LSA-covered group compared with those in LSA-uncovered group. The postoperative systolic pressures of left and right upper limbs were (80.5 ± 37.3)mmHg and (128.7 ± 22.6) mmHg (P = 0.000) in patients with LSA covered completely and were (115.8 ± 25.7)mmHg and (125.5 ± 27.4) mmHg in those with LSA covered partially (P = 1.805). No statistics differences occurred between two groups referring to the mean aortic diameters, incidences of endovascular leakage, post-implantation syndrome (transient elevations of body temperature, C-reactive protein and mild leukocytosis) and incision infection. Transient movement disorder of both lower extremities occurred in two patients in the LSA-uncovered group within the first 24 hours postoperatively, while paraplegia developed in neither group during hospital stay. Patients presented with cooling, discoloration, pain and weakness of left upper extremity and pulselessness of left brachial artery were more often seen in LSA-covered group during perioperative and follow up period. The incidence of cooling, discoloration, pain and weakness of left upper extremity and stroke, together with the mortality had no statistics differences between patients with LSA covered completely or partially. The pulselessness of left brachial dance presented more often (P = 0.000) while the weakness of that presented less often (P = 0.001) in patients with LSA covered completely compared with those with LSA covered partially. No blood vessel by-pass grafting was performed on account of severe left arm ischemia. Conclusions: It is safe and feasible to cover LSA for managing the insufﬁciency of proximal landing zone in patients with Stanford B AD during TEVAR. Better long-term efficacy could be achieved in this way.